The role of ursodeoxycholic acid in the treatment of chemotherapy induced hepatotoxicity in the maintenance treatment of children with acute leukemia - Sibel Tekgündüz; Duygu Yıldırgan; Hüseyin Avni Solgun; Cengiz Bayram; Ali Ayçiçek; Özlem Terzi (SERNEV, 2023)
Introduction: Chemotherapeutic agents used in the treatment of leukemia patients may cause toxic effects in the liver where they are metabolized. Ursodeoxycholic acid (UDCA) is used because of its hepatoprotective effect in the treatment of drug-induced liver toxicity. This study investigated the efficacy of UDCA use, despite the effect of UDCA on tumor cells being unknown, in the treatment of liver toxicity in pediatric patients on chemotherapy for leukemia.Methods: Data from pediatric leukemia patients, who were on maintenance therapy and developed liver toxicity, were retrospectively analyzed. Patients were divided into three groups and the results were compared regarding development of liver toxicity. Patients who were not given UDCA and whose chemotherapy (CT) treatment was interrupted were defined as Group 1, patients who were given UDCA and whose CT was interrupted were defined as Group 2, and patients who were given UDCA and continued CT were defined as Group 3. Results: The study cohort numbered 119 patients, of whom 64 were included in Group 1, 26 patients were in Group 2 and 29 patients were included in Group 3. The mean age of the patients was 6.29±3.03 years and 57.1% of them were male. In Group 1, alanine aminotransferase (ALT) decreased to lt;100 IU/L so UDCA was interrupted, and CT could be rechallenged in 85.9%, in Group 2 this proportion was 100%, and in 69.2% of patients in Group 3, respectively. While there was no significant difference between Group 1 versus Group 2 and Group 1 versus Group 3, a significant difference was found between Group 2 and Group 3 (p=0.005). There were no patients in any group with a bilirubin level of gt;3 mg/dL. Duration for normalization of ALT and aspartate aminotransferase levels were similar. Conclusions: The most effective treatment for chemotherapy-induced liver toxicity in pediatric patients with leukemia seems to be to interrupt CT. It was noteworthy that UDCA administration without interruption of CT treatment, the source of the liver toxicity, was effective in 69.2% of patients. Further and comprehensive studies are needed to evaluate the role of UDCA in hepatoprotection in these patients.Keywords: Ursodeoxycholic acid; leukemia; chemotherapy; hepatotoxicity